1983
DOI: 10.1104/pp.73.2.385
|View full text |Cite
|
Sign up to set email alerts
|

Orientation and Integrity of Plasma Membrane Vesicles Obtained from Carrot Protoplasts

Abstract: Two fractions enriched in plasma membrane derived from suspensioncultured carrot (Daucus carota L.) cells were examined to determine if they differed from each other either in physical nature or in orientation. Parameters studied included the protein composition of purified membranes derived from trypsinized and nontrypsinized protoplasts as well as from trypsinized purified plasma membranes, the effect of inhibitors and membrane perturbants on ATPase activity, the binding of acetyl-14(Cconcanavalin A to purif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

1985
1985
1997
1997

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Thus, the detergent Triton X-100 is now used to determine the sidedness of plasma membrane vesicles (e.g. Randall and Ruesink 1983, Larsson et al 1984, Korner et al 1985, Berczi and M0ller 1986, Hodges and Mills 1986, Yoshida et al, 1986, The assumptions inherent in such an approach will be discussed later.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the detergent Triton X-100 is now used to determine the sidedness of plasma membrane vesicles (e.g. Randall and Ruesink 1983, Larsson et al 1984, Korner et al 1985, Berczi and M0ller 1986, Hodges and Mills 1986, Yoshida et al, 1986, The assumptions inherent in such an approach will be discussed later.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, limited 'attention to markers of other intracellular organelles which may contaminate plasma membrane fractions has compromised the degree of purity of many preparations. Finally, reports referring to the orientation of plasma membrane vesicle preparations obtained by centrifugation methods only describe the presence of mixed populations of right-side-out and inside-out vesicles (Monk et al, 1989;Randall & Ruesink, 1983).…”
Section: Introductionmentioning
confidence: 99%
“…Ultrastructural studies have shown that the surface area of the plasma membrane and endoplasmic reticulum increases extensively in the ectomycorrhizal symbionts (Massicotte et al, 1987;Kottke and Oberwinkler, 1989). This increase is presumably associated with recognition, nutrient trafficking, and secreted protein biosynthesis (Smith and Smith, 1990;Martin and Hilbert, 1991 (Dupont and Leonard, 1980;Randall and Ruesink, 1983 (1983). P tinctorius was grown on Pachlewski's medium in 2% agar (Martin et al, 1990) and C geophilum was grown in liguid culture in Pachlewski's medium (Martin et al, 1983 (1990) and Martin et al (1991).…”
mentioning
confidence: 99%